ANTHROPOMETRIC AND DIETARY ASSESSMENT OF PATIENTS WITH GLYCOGENOSIS TYPE I - Jorge,Natália Bauab (2021)
ABSTRACT Objective: To perform anthropometric and dietary evaluation of patients with glycogenosis type Ia and Ib. Methods: This cross-sectional study is composed of a sample of 11 patients with glycogenosis divided into two subgroups according to the classification of glycogenosis (type Ia=5 and type Ib=6), aged between 4 and 20 years. The analyzed anthropometric variables were weight, height, body mass index, and measures of lean and fat body mass, which were compared with reference values. For dietary assessment, a food frequency questionnaire was used to calculate energy and macronutrients intake as well as the amount of raw cornstarch consumed. Mann-Whitney U test and Fisher’s exact test were performed, considering a significance level of 5%. Results: Patients ingested raw cornstarch in the amount of 0.49 to 1.34 g/kg/dose at a frequency of six times a day, which is lower than recommended (1.75-2.50 g/kg/dose, four times a day). The amount of energy intake was, on average, 50% higher than energy requirements; however, carbohydrate intake was below the adequacy percentage in 5/11 patients. Short stature was found in 4/10 patients; obesity, in 3/11; and muscle mass deficit, in 7/11. There were no statistical differences between the subgroups. Conclusions: In patients with glycogenosis type I, there was deficit in growth and muscle mass, but no differences were found between the subgroups (Ia and Ib). Although the diet did not exceed the adequacy of carbohydrates, about 1/3 of the patients presented obesity, probably due to higher energy intake.